THE RATIO OF INDICATORS OF FIGHTING IN SITUATIONS OF DIFFERENT LEVELS OF INTENSITY - A. Nuritdinov (Journals Park Publishing, 2023)
The article presents the analysis of training and competition fights of highly qualified taekwondo players.
Keywords: Athlete training, high performance, high performance, physical training, technical-tactical actions, competition, offensive actions, impact, sports achievements.